A contribuição do cinema militante em processos de construção de identidades e territórios no contexto da metrópole: o movimento dos trabalhadores sem teto na periferia de São Paulo - Tedesco, Marina Cavalcanti (2009)
In 2005, the Movimento dos Trabalhadores Sem Teto (Homeless Workers Movement), operating in the São Paulo state since the 90 s, created its Brigada de Guerrilha Cultural (Cultural Guerrilla Brigade). The brigade responsability was to create, through different activities (including theatre, music, poetry, movie making, etc), the moviment s own political culture which was supposed to work, at the same time, as advertising, insurrection s agent and militant s expression. It lasted until 2007. This dissertation s subject is the cinema made within this context. Its prime purpose is to investigate how the movies, taking part in a political and cultural project that is articulated in a wider scope, help in the construction process of new identities and territories. The filmic corpus of this investigation, thus, is: Chico Mendes a dignidade não se rende (2005) and Direitos Esquecidos (2005) Chico Mendes Occupation (Taboão da Serra, 2005-2006), Vídeo-Informe 1 (2007), Vídeo- Informe 2 (2007) and Vídeo-Informe 3 (2007) João Cândido Occupation (Itapecerica da Serra, 2007) and Construindo o poder popular (2008) Silvério de Jesus Occupation (Embu das Artes, 2008).